Pengaruh konsentrasi ekstrak daun pare (momordica charantia l.) terhadap kematian larva aedes aegypti - Halim, Rahmawati; Toemon, Agnes Immanuela; Ysrafil, Ysrafil; Fatmaria, Fatmaria; Turnip, Oktaviani Naulita (Poltekkes Kemenkes Aceh, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a health problem in Indonesia, transmitted by the Aedes aegypti mosquito. Bitter melon leaves contain active compounds such as saponins, alkaloids, and flavonoids belived to be effective as larvacides and are expected to serve as a more environmentally friendly alternative for mosquito control in preventing the spread of DHF.Objective: To determine the potential of natural biolarvacide from bitter melon leaf extract (Momordica charantia L.) against Aedes aegypti larvae.Methods: An experimental study was conducted at the Public Health Laboratory of Tanah Bumbu in July 2024. This experimental research used 375 Aedes aegypti larvae with five treatments and three repetitions, observing the number of larvae that died after 24 hours. The data were analyzed using the Shapiro-Wilk test, Levene's test, Kruskal-Wallis test, Mann-Whitney test, and probit analysis.Results: Bitter melon leaf extract at concentrations of 0,3% and 0,6% did not cause larval death, so it was not effective in inhibiting the growth of Aedes aegypti. While at concentrations of 0,9% showed a significant effect in inhibiting larval growth. The results of the Kruskal-Wallis test on the death of larvae treated with bitter melon leaf extract obtained a significance value of 0,008 (p <0,05). The results of the Mann-Whitney test showed that there was a significant difference between the concentration of 0,9% bitter melon leaf extract and the positive control abate, as well as between the negative control aquadest and the concentration of 0,9% bitter melon leaf extract. The results of the probit analysis test obtained an LC50 value of 1,202%.Conclusion: The 0.9% concentration of bitter melon leaf extract can inhibit the growth of Aedes aegypti larvae. However, it is not yet suitable as an alternative bio-larvicide.